Theoretical determination of corrosion inhibitor activities of 4-allyl-5-(pyridin-4-yl)-4H-1,2,4-triazole-3-thiol-thione tautomerism - Koparir, Pelin; Omer, Rebaz Anwar; Karatepe, Arzu; Ahmee, Lana Omer (Natl Inst Science Communication-Niscair, 2022)
Using the density functional method B3LYP/6-311G(d,p) calculations, the inhibitor activity of 4-allyl-5-(pyridin-4-yl)-4H-1,2,4-triazole-3-thiol tautomerism against corrosion of neutral copper surfaces has been investigated. Among the inhibitors tested, the 4-allyl-5-(pyridin-4-yl)-4H-1,2,4-triazole-3-thiol inhibitor has the inhibition performance for both forms (thiol and thione). Quantum chemical parameters that are correlated to the inhibition efficiency including highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital, (LUMO), energy bandgap (Delta E), electronegativity (chi), Hardness (eta), softness (sigma), dipole moment (mu), the fraction of the electrons transferred (Delta E), and Total energy (TE) has been calculated. In addition, the adsorption of inhibitors on the neutral copper surface reveals that nitrogen adsorption is preferred over sulfur adsorption. The results show that the thione form has the highest inhibitor compared to the thiol form.
Keywords: 1,2,3 Triazole; DFT; Corrosion Inhibitor Activity; Tautomerism